Synthesis, characterization and cytotoxicity studies of nanocrystalline cellulose from the production waste of rubber-wood and kenaf-bast fibers - Tuerxun, Duolikun; Pulingam, Thiruchelvi; Nordin, Nurul Izza; Chen, You Wei; Kamaldin, Jahangir; Julkapli, Nurhidayatullaili Muhd; Lee, Hwei Voon; Leo, Bey Fen; Johan, Mohd Rafie (Elsevier, 2019)
In the present study, nanocrystalline cellulose (NCC) was successfully prepared from raw rubberwood fiber (RRaw) and raw Kenaf-bast fiber (KRaw) via a series of multi-step chemical-mechanical purification techniques, namely, alkalization treatment, hydrogen peroxide bleaching and acid hydrolysis. The obtained nanocellulose yields were 27.51% and 32.53% for RRaw and KRaw, respectively. The crystallinity index of the RRaw and KRaw based nanocellulose increased from 61.21% to 74.34% and 54.12% to 73.19%, respectively, after acid hydrolysis. Morphological characterization by scanning electron microscopy (SEM) and transmission electron microscopy (TEM) clearly showed the formation of rod-shaped NCC with an average diameter of 5.14 ± 1.91 nm and 5.27 ± 2.38 nm for RRaw and KRaw, respectively. Their size distributions significantly reduced compared to raw cellulose biomass fiber and extracted cellulose (EC). Furthermore, changes in the Fourier transform-infrared (FTIR) peaks showed that amorphous regions (e.g. hemicelluloses and lignin) were successfully removed from the fibre surface. The thermogravimetric analysis (TGA) of as-synthesized NCC confirmed its thermostability. Cytotoxicity tests demonstrated that NCC did not exhibit cellular toxicity upon exposure to macrophages (RAW 264.7) and HaCaT cells up to 700 µg mL−1. © 2019 Elsevier Ltd